Conversations on the Global South – Universalizing Local Values Through “Lifting Up” - Zialcita, Fernando N. (Archīum Ateneo, 2020)
Work on Philippine values has focused on either 1) identifying shared values or on 2) proposing needed values. While these are both important, this paper has a different focus. It proposes that everyday particularistic values, which other authors have identified, could serve as bridges to more abstract, universal values. The model used is Hegel’s dialectical “lifting up” (Aufhebung) of a concept to a higher level. (This I translate into Tagalog as “pag-aangat.”) As such this discussion of universalizing traditional particularistic values is significant to the wider public, for we all face the challenge of adapting to new circumstances while retaining one’s identity. This paper reviews three cases where a “lifting up” occurs implicitly: 1) Albert Alejo’s dialogic seminars on the value of utang na loob (a client’s feeling of indebtedness toward a patron) invert a relationship of dependency by demonstrating that the patron actually depends on the client; 2) the teachings (turo or aral) of three heroes of the Philippine Revolution invite all to discover that concern for the family is unrealizable without concern for the nation; 3) during the People Power Revolution of 1986, activists used pakikisama (harmonizing the self with a group) to draw multitudes to resist the dictatorship and to vivify abstractions like “freedom” and “justice.” The paper recommends that Alejo’s dialogic seminars could be one way to vivify universal values by using familiar values as starting points. Dialogic seminars could flesh out the sketches by the heroes or discuss how a narrow value, like pakikisama, can become a gateway to a broader one.